iTechnology as cure or iTechnology as empowerment: What do North American news media report? - Haller, Beth; Jones, Chelsea Temple; Naidoo, Vishaya; Blaser, Art; Galliford, Lindzey (Disability Studies Quarterly, 2016)
<!–[if gte mso 9]> <![endif]–> With the growth of tablet technology as a communication method for many people with disabilities, the news media have created new narratives about disability, as well as reinforcing older narratives. This project evaluates U.S. and Canadian print news media coverage of people with communication disabilities and iTechnology (Apple products), as well as other new tablet and smart phone technology, being used as communication devices. Using qualitative analysis, the project investigates media coverage since 2007, when the first iPhone was available, through 2012 (N=98). Themes evaluated in the stories were related to the medical model, the social model, and the Supercrip model, as well as investigating economic models related to the expense of and access to iTechnology. These media stories are rich texts that illustrate how news narratives about disability are changing, especially when disability stories intersect with the new hot topic of iTechnology. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>